CONCEPTS OF RAGA ELABORATION IN INDORE GHARANA: AN ANALYSIS - Malhotra, Nakul (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The gharana system occupies a central position in the evolution and transmission of Hindustani classical music, shaping stylistic identities within the broader framework of raga performance. Among these traditions, the Indore Gharana, most prominently associated with Ustad Amir Khan, is distinguished by its introspective, vilambit-oriented, and architecturally expansive approach to raga development. This paper examines the conceptual foundations and performance techniques underlying raga elaboration in the Indore Gharana, with particular emphasis on alap, bol-baant, nom-tom, and taan structures. Through analytical study of selected recordings, textual sources, and musicological commentary, the research explores how the Indore style constructs a gradual and meditative unfolding of the raga. Special attention is given to its emphasis on slow tempo (ati-vilambit), meend-dominant melodic movement, merukhand-based permutation techniques, and the restrained yet intricate use of taans. The study also investigates how bol-baant and nom-tom elements are integrated into khayal performance to enhance structural coherence and aesthetic depth. By situating these practices within the larger discourse of gharana tradition, the paper argues that the Indore Gharana represents a distinctive model of raga vistaar that balances rigorous structural logic with profound emotional expressivity. The findings contribute to a deeper understanding of stylistic individuality within Hindustani music and highlight the continuing relevance of gharana-based aesthetics in contemporary performance contexts.